Development of regional innovation environment in the northern part of Czechia - Hlaváček, Petr (Rozwój środowiska regionalnych innowacji w północnej części Czech, 2017)
The article focuses on the analysis of the innovation environment of the regions in Czechia, focusing on the Ústí Region. Due to the geographical location of the Ústi Region and its economic development and structure, regions which went through similar economic and social development have been selected for research in this article, in particular the Karlovy Vary Region, the Liberec Region, and the Moravia-Silesia Region. The analysis has used the indicators from the field of human resources, employment in R&D, information technologies, as well as education. It is obvious under the comparison of the selected parameters that the Ústí Region lags in the development of the innovation potential behind the Liberec Region and Moravia-Silesia Region, but reports better results and development changes compared to the Karlovy Vary Region
Biblioteka Regionalisty, 2017, Nr 17, s. 43-54
Keywords: innovation environment; region; Czechia; środowisko innowacyjne; Czechy